Revitalisasi Pasar Tradisional Sebagai Upaya Meningkatkan Kualitas Hidup Masyarakat di Kecamatan Pasimarannu Kabupaten Kepulauan Selayar Provinsi Sulawesi Selatan - Sultan, Andi (Jurnal Ekonomi Balance, 2014)
Andi Sultan, 2018. Title, "Revitalization of Traditional Markets as an Effort to Improve the Quality of Life of Communities in Pasimarannu District, Selayar Islands Regency, South Sulawesi Province. This research aims to find out the effects of traditional market revitalization on people's welfare in Pasimarannu Subdistrict, Kepulaun Selayar Regency. The type of research used is descriptive qualitative method. Data collection techniques use observation and interview techniques. The results of the research show that with the revitalization of traditional markets, market activities are increasingly centralized, and the level of community satisfaction has also reflected increased welfare.